Why have some countries become more unemployed than others? An investigation of changes in unemployment in EU member states since 2008 - Myant, Martin; Piasna, Agnieszka (Brussels, 2014)
" This Working Paper investigates links between employment changes and both sectoral developments and changes in earnings levels in six EU member states. The paper challenges the view that a remedy focusing on reducing employment protection and pay levels leads to higher levels of employment. It recommends instead policies to restore investment levels and to help transformation towards economies based on higher skill and qualification levels. "